Reduced Chlorine in Drinking Water Distribution Systems Impacts Bacterial Biodiversity in Biofilms - Bertelli, Claire; Courtois, Sophie; Rosikiewicz, Marta; Piriou, Philippe; Aeby, Sébastien; Robert, Samuel; Loret, Jean-François; Greub, Gilbert (Frontiers in Microbiology, 2018)
In drinking water distribution systems (DWDS), a disinfectant residual is usually applied to limit bacterial regrowth. However, delivering water with no or reduced chlorine residual could potentially decrease the selection for antimicrobial resistant microorganisms, favor bacterial regrowth and result in changes in bacterial populations. To evaluate the feasibility of water reduction in local DWDS while ensuring water safety, water quality was measured over two months in two different networks, each of them harboring sub-areas with normal and reduced chlorine. Water quality remained good in chlorine reduced samples, with limited development of total flora and absence of coliforms. Furthermore, 16S rRNA amplicon-based metagenomics was used to investigate the diversity and the composition of microbial communities in the sub-networks. Taxonomic classification of sequence reads showed a reduced bacterial diversity in sampling points with higher chlorine residuals. Chlorine disinfection created more homogeneous bacterial population, dominated by Pseudomonas, a genus that contains some major opportunistic pathogens such as P. aeruginosa. In the absence of chlorine, a larger and unknown biodiversity was unveiled, also highlighted by a decreased rate of taxonomic classification to the genus and species level. Overall, this experiment in a functional DWDS will facilitate the move towards potable water delivery systems without residual disinfectants and will improve water taste for consumers.